2018
DOI: 10.1097/md.0000000000013120
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term safety and immunogenicity of the M72/AS01E candidate tuberculosis vaccine in HIV-positive and -negative Indian adults

Abstract: Objectives:To assess the long-term safety and immunogenicity of the M72/ Adjuvant System (AS01E) candidate tuberculosis (TB) vaccine up to 3 years post-dose 2 (Y3) in human immunodeficiency virus (HIV)-positive (HIV+) and HIV-negative (HIV−) Indian adults.Methods:This phase II, double-blind, randomised, controlled clinical trial (NCT01262976) was conducted at YRG CARE Medical Centre, in Chennai, India, between January 2011 and June 2015.Three cohorts (HIV+ participants stable on antiretroviral therapy [ART; HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 22 publications
1
22
1
Order By: Relevance
“…Several types of preclinical studies have verified that humoral immunity may give protection against M. tuberculosis ( 53 55 ). M72/AS01 E vaccination-induced M72-specific antibodies persisted for a maximum of 3 years ( 56 ). In particular, two-doses of the vaccination seem to have strong long-term protection.…”
Section: Discussionmentioning
confidence: 99%
“…Several types of preclinical studies have verified that humoral immunity may give protection against M. tuberculosis ( 53 55 ). M72/AS01 E vaccination-induced M72-specific antibodies persisted for a maximum of 3 years ( 56 ). In particular, two-doses of the vaccination seem to have strong long-term protection.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there was a sharp increase in the seroconversion rates after the second vaccine dose compared with the first. Kumarasamy et al reported that M72-specific antibodies induced through vaccination with M72/AS01 E persisted for a maximum of 3 years (27). Notably, two-dose vaccination offered more durable long-term protection.…”
Section: Discussionmentioning
confidence: 99%
“…M72/AS01 E showed an acceptable safety profile and did not affect HIV viral load or CD4 cell counts in HIV-infected Swiss adults, most of whom were receiving ART (Thacher et al, 2014). In a second trial in India, M72/AS01 E vaccination was well tolerated and induced a polyfunctional M72-specific CD4 T-cell response that persisted through 1 year, and which was higher in patients receiving ART compared to those who were ART-naïve (Kumarasamy et al, 2016(Kumarasamy et al, , 2018. However, the crux of the problem is that the period of maximal risk for HIV-associated TB is the period prior to immune reconstitution, before starting ART (Lawn et al, 2009).…”
Section: Hiv Infectionmentioning
confidence: 97%
“…Live mycobacterial vaccines like BCG, VPM1002, and MTBVAC have an unfavorable risk profile for persons with HIV infection (Hesseling et al, 2008); and therefore inactivated mycobacterial, viral-vectored and proteinsubunit candidate vaccines, including M72/AS01 E , might be more appropriate for vaccination of individuals with HIV and other immune-suppressive conditions (Thacher et al, 2014;Kumarasamy et al, 2016Kumarasamy et al, , 2018. Studies of vaccination of HIV-infected individuals have reported lower induced immune responses, compared to HIV-uninfected individuals, which were partly restored by antiretroviral therapy (ART) (Thacher et al, 2014;Kumarasamy et al, 2016Kumarasamy et al, , 2018. M72/AS01 E showed an acceptable safety profile and did not affect HIV viral load or CD4 cell counts in HIV-infected Swiss adults, most of whom were receiving ART (Thacher et al, 2014).…”
Section: Hiv Infectionmentioning
confidence: 99%